Annual Report 1980-81 - Planning Commission (Planning Commission Government of India, 1981)
The Planning Commission Reports for 1980-81 detail the reconstitution of the Commission under Smt. Indira Gandhi and the development of the Sixth Five-Year Plan (1980-85), along with the Annual Plan for 1981-82. The reports highlight a collaborative planning process involving central and state governments, economists, and social scientists. Key activities included evaluations of irrigation projects, rural water supply, employment schemes, and investment proposals for public sector projects. Divisional work spanned perspective planning, economic analysis, financial resource estimation, project appraisal, education, agriculture, and energy. Special focus was placed on backward classes through targeted development programs. The reports emphasize the enhancement of training and evaluation capacity to improve policy implementation. Overall, they reflect India’s commitment to inclusive, evidence-based, and coordinated socioeconomic planning.
Government of India Planning Commission
Keywords: Planning Commission; Sixth Five-Year Plan; Annual Plan; Programme Evaluation; Agriculture; Rural Development; Economic Planning; Power and Energy; Education; Social Welfare